The Urgence of Ta'lim Muta'allim, Character, and Student's Learning Motivation: Urgensi Ta’lim Muta’allim, Karakter, Serta Motivasi Belajar Peserta Didik - Hoeruman, Muhammad Restu (CV. Media Publikasi Profesional, 2023)
This study aims to analyze the influence of Ta’lim al-Muta’allim literacy on character education and students’ learning motivation at a Madrasah Aliyah. Using a descriptive qualitative method, data were collected through observation, interviews, and documentation involving 106 students. The findings show that values such as ta’dzim (respect for teachers), responsibility, and discipline found in the book positively affect students’ learning behavior and attitudes toward teachers and school rules. This study confirms the pedagogical relevance of classical Islamic texts in modern education. It recommends the integration of Ta’lim al-Muta’allim into the Islamic Religious Education curriculum as a contextual and applicable strategy for character building.